2013
DOI: 10.1121/1.4792936
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mismatched place-of-stimulation on the salience of binaural cues in conditions that simulate bilateral cochlear-implant listening

Abstract: Although bilateral cochlear implantation has the potential to improve sound localization and speech understanding in noise, obstacles exist in presenting maximally useful binaural information to bilateral cochlear-implant (CI) users. One obstacle is that electrode arrays may differ in cochlear position by several millimeters, thereby stimulating different neural populations. Effects of interaural frequency mismatch on binaural processing were studied in normal-hearing (NH) listeners using band-limited pulse tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
129
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(149 citation statements)
references
References 44 publications
(80 reference statements)
18
129
2
Order By: Relevance
“…By varying stimulus duration with carrier frequency, a constant "cochlear bandwidth" of ϳ3 mm (Ϯ1.5 mm), simulating the estimated average spread of excitation along the cochlea for a single electrode, can be maintained (cf. Goupell et al 2013;Kan et al 2013). While Gabor clicks provide a reasonable acoustic simulation of the CI pulsatile stimuli in terms of bandwidth, their comparability to CI stimuli is limited by their duration: At 4-kHz center frequency, the duration of a single pulse is nearly two orders of magnitude greater than the duration of a CI electrical pulse.…”
Section: Nh Stimuli and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…By varying stimulus duration with carrier frequency, a constant "cochlear bandwidth" of ϳ3 mm (Ϯ1.5 mm), simulating the estimated average spread of excitation along the cochlea for a single electrode, can be maintained (cf. Goupell et al 2013;Kan et al 2013). While Gabor clicks provide a reasonable acoustic simulation of the CI pulsatile stimuli in terms of bandwidth, their comparability to CI stimuli is limited by their duration: At 4-kHz center frequency, the duration of a single pulse is nearly two orders of magnitude greater than the duration of a CI electrical pulse.…”
Section: Nh Stimuli and Proceduresmentioning
confidence: 99%
“…1). Such "Gabor clicks" have previously been used to simulate the brief yet effectively narrowband nature of CI pulsatile stimuli (e.g., Goupell et al 2013). By varying stimulus duration with carrier frequency, a constant "cochlear bandwidth" of ϳ3 mm (Ϯ1.5 mm), simulating the estimated average spread of excitation along the cochlea for a single electrode, can be maintained (cf.…”
Section: Nh Stimuli and Proceduresmentioning
confidence: 99%
“…Understandably, place of articulation perception is particularly difficult for people with hearing impairment (Bilger and Wang, 1976), including people with CIs (Munson et al, 2003), and is a particularly difficult feature to recover when spectral quality is experimentally degraded for listeners with NH (Friesen et al, 2001;Xu et al, 2005). When conducting studies with NH individuals, resolution in the spectral domain can be explicitly controlled using noise vocoders (Shannon et al, 1995;Friesen et al, 2001;Xu et al, 2005), sine vocoders (Dorman and Loizou, 1997), Gaussian envelope tone vocoders (Goupell et al, 2013), and also with other methods used to achieve spectral smearing (ter Keurs et al, 1993). In these studies, place of articulation consistently emerges as a difficult feature to recover.…”
Section: A Previous Measures Of Spectral Resolution In CI Listenersmentioning
confidence: 99%
“…The study of Goupell and coworkers (Goupell et al, 2013) in normal-hearing listeners showed robust lateralization responses, by using stimuli with an interaural mismatch in center frequency up to 4 kHz in one ear, and 14 kHz in the other. Francart and Wouters (2007) demonstrated ILD sensitivity in normal-hearing listeners for signals with an interaural frequency mismatch of up to one octave.…”
Section: Introductionmentioning
confidence: 99%